(untitled) - Guirdham, Maureen; Wierzbicka, Anna (Palgrave Macmillan, 2009)
Ebook from Proquest
Keywords: Business culture; Business Etiquette; Doanh nghiệp -- Kinh doanh -- Văn hóa; Văn hóa kinh doanh